Function of Russin words Ideologime – to strenthen imperialistic identity - Girkontas , Robertas (Genocidas ir rezistencija, 2018)
In 2013–2014, Russian President Vladimir Putin and other government officials started increasingly using the term ‘Russian world’ in public statements. However, they all avoided giving a precise definition of the term. The vagueness and obscurity of the concept of the Russian world makes it possible to unite all those who believe in Russia’s exceptionalism and its messianic role – communists and monarchists, globalists and eurasianists, nationalists and internationalists, even though their views are completely incompatible on other issues. The ideology of the Russian world, whether the term will be used or abandoned, is and will remain at the core of Putin’s ‘ideology’, which legitimises authoritarianism and justifies Russia’s claim to a special role in the creation of a new world order.
Keywords: Russia; post-soviet territory; imperialism; propaganda